2020
DOI: 10.1016/j.redox.2020.101733
|View full text |Cite
|
Sign up to set email alerts
|

Acid enhancement of ROS generation by complex-I reverse electron transport is balanced by acid inhibition of complex-II: Relevance for tissue reperfusion injury

Abstract: Generation of mitochondrial reactive oxygen species (ROS) is an important process in triggering cellular necrosis and tissue infarction during ischemia-reperfusion (IR) injury. Ischemia results in accumulation of the metabolite succinate. Rapid oxidation of this succinate by mitochondrial complex II (Cx-II) during reperfusion reduces the co-enzyme Q (Co-Q) pool, thereby driving electrons backward into complex-I (Cx-I), a process known as reverse electron transport (RET), which is thought to be a major source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…Furthermore, mitochondria are important sources of ROS generation, and accumulation of high ROS levels induces cell apoptosis. 58 As baicalein treatment upregulated the mitochondrial number, OHT in combination with baicalein resulted in significant mitochondria‐associated ROS generation and exacerbated intracellular ROS accumulation, causing loss of MMP and leading to apoptosis in TAM‐resistant cells. Importantly, the active oxygen scavenger NAC reversed the pro‐apoptotic effect of combined baicalein and TAM treatment of TAM‐resistant cells, implying that ROS are the critical mediator involved in this apoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, mitochondria are important sources of ROS generation, and accumulation of high ROS levels induces cell apoptosis. 58 As baicalein treatment upregulated the mitochondrial number, OHT in combination with baicalein resulted in significant mitochondria‐associated ROS generation and exacerbated intracellular ROS accumulation, causing loss of MMP and leading to apoptosis in TAM‐resistant cells. Importantly, the active oxygen scavenger NAC reversed the pro‐apoptotic effect of combined baicalein and TAM treatment of TAM‐resistant cells, implying that ROS are the critical mediator involved in this apoptotic effect.…”
Section: Discussionmentioning
confidence: 99%
“…These results demonstrate that SDH inhibition during I/R injury blocks the SDH-mediated succinate accumulation, thus protecting the heart against the redox insult during I/R injury. Interestingly, a recent study demonstrated that succinate accumulation in ischemia/reperfusion is not due to the reverse activity of SDH, but rather due to canonical TCA cycle activity (108). Thus, although succinate accumulation during ischemia is conserved across vertebrates, the proposed mechanism of succinate accumulation remains to be further understood.…”
Section: Tca Cycle Metabolites In the Heartmentioning
confidence: 99%
“…In addition, the generation of O 2 · − can also be caused by reverse electron transport (RET) in complex I when the pool of CoQ becomes over-reduced with electrons from complex II. In RET process, electrons first enter complex II through succinate oxidation and reach CoQ, and then are directed back to complex I instead of proceeding forward to complex III [ 47 , 82 , 94 ]. Succinates from ischemic accumulation are rapidly re-oxidized by the succinate dehydrogenase of complex II, which transfers electrons from complex II to complex I, and produces O 2 ·− [ 90 , 95 ].…”
Section: Pathological Mechanism Of Myocardial Ischemia Reperfusion Injurymentioning
confidence: 99%